Water-Energy Nexus: Evaluating the Effects of Climate Change on Energy and Water Sources Development in Liberia - Zaizay, Amos; Gökçekuş, Huseyin (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
The interactions between water and energy in Liberia under the water-energy nexus approach are considered in this study, focusing on the challenges and possibilities of these links. It assesses the climate-related issues concerning Liberian water systems including temperature, rainfalls, and available water amounts. It assesses the balance and the utilization of water in the climate change framework. Cross-sectional and meta-analysis model was used in this study. It addresses the vulnerability, particularly the damages to hydropower, energy production, and fisheries in Liberia. There are numerous water resources in Liberia however, there is a disconnect with regards to the availability of data and an effective water-energy monitoring. Additionally, also show coordination in water and energy projects. A sustainable use of water, an installation of eco-friendly electricity production sources and adaptation to climate changes is slowly being pursues as the country boast high renewable energy potential especially with regards to hydropower. The study finds high rainfall with projections that it may reduce and also limited access to water and electricity. The study also finds gradual increase in energy generation and a higher renewable energy generation. Finally, possible pathways for a multidimensional approach and technology including policing to continue sustaining Liberia under a complex climate-water-energy nexus are presented. These issues are questions of transformation within the relationships between energy systems, water resources, and climate transition.